2012
DOI: 10.4067/s0034-98872012001000002
|View full text |Cite
|
Sign up to set email alerts
|

Asociación entre polimorfismos del gen de adiponectina y estado nutricional en escolares de la comuna de Hualpén

Abstract: Association between adiponectin gene polymorphisms and obesity in school age children from Hualpén, Chile (Rev Med Chile 2012; 140: 1245-1252.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hara et al [27] reported that individuals with the TG or GG genotype at position 45 have a higher risk of developing DM2 when compared to those of the TT genotype. Therefore, individuals with the G allele of the þ45T > G variant in ADIPOQ gene have lower plasma levels of adiponectin [24], which was observed in the studied SCT group. Although, without difference in the frequency of MS, the TT þ TG SCT group may present a higher risk of worsening in the long-term cardiometabolic profile, and even of MS. On the other hand, Sanch es et al [28] suggested that the presence of the G allele has a protective effect in individuals with DM2 and MS.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Hara et al [27] reported that individuals with the TG or GG genotype at position 45 have a higher risk of developing DM2 when compared to those of the TT genotype. Therefore, individuals with the G allele of the þ45T > G variant in ADIPOQ gene have lower plasma levels of adiponectin [24], which was observed in the studied SCT group. Although, without difference in the frequency of MS, the TT þ TG SCT group may present a higher risk of worsening in the long-term cardiometabolic profile, and even of MS. On the other hand, Sanch es et al [28] suggested that the presence of the G allele has a protective effect in individuals with DM2 and MS.…”
Section: Resultsmentioning
confidence: 59%
“…There are no previous studies associating the effect of the G allele of þ45T > G variant in ADIPOQ gene on adiponectin concentrations in SCT, however, it has been shown that it can alter adiponectin concentrations in other diseases and populations. The þ45T > G variant in ADIPOQ gene has been linked to the development of DM2, insulin resistance, obesity, coronary artery disease [23] and hypoadiponectinemia [24]. Paradoxically, in another type of hemoglobinopathy, beta-thalassemia, studies show that adiponectin levels are high, raising questions about their pro or anti-inflammatory role in this disease [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported that subjects with the T/G or G/G genotype at position 45 have a higher risk of developing DM2 when compared to those with T/T genotype 20 . Likewise, it has been observed that subjects who present the G allele of the +45T>G polymorphism have lower plasma levels of adiponectin 19 .…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have determined that different polymorphisms (SNPs) have been located in the adiponectin gene, which can affect both the transcription and the activity of this hormone. Among the most prominent are the polymorphisms +45 T>G, +276 G>T, -11.377 C>G and -11.391 G>A 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation